Qur'anic Exegesis in the Digital Sphere: The Dynamics of Authority, Audience, and Algorithms on Individual and Collective Platforms - Muhammad Nur Rhafik; Moh. Yardho; Abdullah Qohi; Nur Rohmat; Surya Saputra Mahmud; Muhammad Ihsan Mahbub (QiST: Journal of Quran and Tafseer Studies, 2026)
Purpose - This study investigates how Qur'anic exegesis (tafsīr) is produced, disseminated, and legitimized in the digital sphere by examining the interaction among religious authority, audience participation, and algorithmic mediation across individual and collective digital platforms. Design/methodology/approach - A qualitative digital content analysis was conducted on 25 tafsīr contents selected through purposive sampling from YouTube, TikTok, Instagram, Facebook, and Islamic websites. Data were analyzed using thematic and descriptive-analytical methods. The study employs Heidi Campbell's Digital Religion, Max Weber's theory of authority, and Stig Hjarvard's mediatization of religion as analytical frameworks. Findings - The findings reveal two dominant models of digital tafsīr dissemination. Individual platforms rely primarily on charismatic religious figures as sources of legitimacy, while collective platforms derive authority from institutional credibility and editorial mechanisms. Audience participation extends beyond content consumption to content redistribution and reinterpretation, positioning users as prosumers. Furthermore, platform algorithms significantly influence content visibility, popularity, and patterns of fragmented religious consumption. The study demonstrates that digital tafsīr operates within a hybrid ecosystem where traditional, charismatic, and legal-rational forms of authority interact and coexist. Research implications/limitations - The study is limited to 25 digital tafsīr samples and focuses primarily on Indonesian digital platforms. Consequently, the findings may not fully represent broader global Muslim digital environments. Future studies may employ larger datasets and comparative cross-national approaches. Originality/value - This study contributes to the growing field of digital tafsīr by integrating religious authority, audience participation, and algorithmic mediation into a single analytical framework. It highlights algorithms as influential socio-technical actors in shaping the visibility, legitimacy, and circulation of Qur'anic interpretation in contemporary digital culture.